Platonova filozofija umetnosti in slovenska književnost - Fridl, Ignacija J. (Primerjalna književnost, 2009)
The treatise presents a detailed analysis of relevant interpretations of Plato's stance of art. It differs from them in that it understands Plato's mimesis ontologically, as the human being's disclosedness in its ontological openness amidst finitude and infinity, in which human boundaries, including those of artistic creative freedom, are revealed. On the basis of such understanding, the treatise opens up a new research field on Platonism in Slovene literature, which up to this point paid attention but to individual writers (Prešeren, Stritar, Bartol...).
Keywords: Plato, 427-347 pr.n.š.; aesthetics; estetika; filozofija umetnosti; platonizem; mimesis; Slovene literature; slovenska književnost